Reproductive Health Education Package to Reduce Risky Sexual Behaviors among Undergraduates in Selected State Universities in Sri Lanka: A Controlled Trial (Global Journal of Medical Research, 2019)
Abstract not found
Keywords: health education; randomization; reproduction; sexual behaviors; undergraduates